Effects of vitamin E, vitamin C and polyphenols on the rate of blood pressure variation: Results of two randomised controlled trials - Hodgson, J.; Croft, K.; Woodman, R.; Puddey, I.; Bondonno, C.; Wu, J.; Beilin, L.; Lukoshkova, E.; Head, G.; Ward, Natalie (2014)
High blood pressure (BP) variability, which may be an important determinant of hypertensive end-organ damage, is emerging as an important predictor of cardiovascular health. Dietary antioxidants can influence BP, but their effects on variability are yet to be investigated. The aim of the present study was to assess the effects of vitamin E, vitamin C and polyphenols on the rate of daytime and night-time ambulatory BP variation. To assess these effects, two randomised, double-blind, placebo-controlled trials were performed. In the first trial (vitamin E), fifty-eight individuals with type 2 diabetes were given 500 mg/d of RRR-α-tocopherol, 500 mg/d of mixed tocopherols or placebo for 6 weeks. In the second trial (vitamin C–polyphenols), sixty-nine treated hypertensive individuals were given 500 mg/d of vitamin C, 1000 mg/d of grape-seed polyphenols, both vitamin C and polyphenols, or neither (placebo) for 6 weeks. At baseline and at the end of the 6-week intervention, 24 h ambulatory BP and rate of measurement-to-measurement BP variation were assessed. Compared with placebo, treatment with α-tocopherol, mixed tocopherols, vitamin C and polyphenols did not significantly alter the rate of daytime or night-time systolic BP, diastolic BP or pulse pressure variation (P>0·05). Treatment with the vitamin C and polyphenol combination resulted in higher BP variation: the rate of night-time systolic BP variation (P= 0·022) and pulse pressure variation (P= 0·0036) were higher and the rate of daytime systolic BP variation was higher (P= 0·056). Vitamin E, vitamin C or grape-seed polyphenols did not significantly alter the rate of BP variation. However, the increase in the rate of BP variation suggests that the combination of high doses of vitamin C and polyphenols could be detrimental to treated hypertensive individuals.